2020
DOI: 10.31838/jcr.07.02.17
|View full text |Cite
|
Sign up to set email alerts
|

International Financial Reporting Standards and Earnings Management: Comparative Study of Pre-Post Full Convergence of Ifrs in Malaysia

Abstract: Purpose -The purpose of this study is to examine the influence of full convergence of IFRS (International Financial Reporting Standards) on earnings management using a sample of companies listed on Bursa Malaysia given that the rationale for adoption of IFRS in Malaysia was to make the published financial statements of public listed companies more transparent and comparable. Design/Methodology/Approach -A sample of 200 firms listed on Bursa Malaysia (Malaysian Stock Exchange) were chosen to investigate and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The implementation of IFRS, they indicated at the study's conclusion, may be able to lessen the use of EM practises during a financial crisis. In a recent study, Garrett et al (2020) investigate whether the adoption of IFRS in Malaysia had any impact on Earnings Management procedures. Their findings revealed that, following the full convergence of IFRS, there had been a downward tendency in earnings management across the Malaysian industrial sector.…”
Section: Earnings Management and The Covid-19 Pandemicmentioning
confidence: 99%
“…The implementation of IFRS, they indicated at the study's conclusion, may be able to lessen the use of EM practises during a financial crisis. In a recent study, Garrett et al (2020) investigate whether the adoption of IFRS in Malaysia had any impact on Earnings Management procedures. Their findings revealed that, following the full convergence of IFRS, there had been a downward tendency in earnings management across the Malaysian industrial sector.…”
Section: Earnings Management and The Covid-19 Pandemicmentioning
confidence: 99%
“…Earnings management is a mechanism in which financial decisions are made on intentional assumptions that are consistent with the financial reporting process as well as the main objective behind which is referred to as deception, concealment, or data manipulation, thereby giving a boost to earnings management [20]. According to Healy and Wahlen [24], the reason for this conduct is to confuse shareholders and stakeholders in order to extract advantageous outcomes from company contracts using distorted accounting information.…”
Section: Literature Review and Hypothesis Development 21 Earnings Managementmentioning
confidence: 99%
“…The International Financial Reporting Standards (IFRS) embodies the highest quality accounting principles to improve financial reporting transparency and comparability (Wahyuningtyas, 2018) [45]. Garrett et al [20] stated that the idea of financial statements is to inform users about the true and fair status of companies. However, companies in practice tend to mislead people when facing crises by not reporting their current status and manipulating financial reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation